Turkish journal of veterinary & animal sciences: Editorial - Üniversitesi, Firat; Fakültesi, Veteriner; Dali, Doum Ve Jinekoloji Anabilim; Elazi.-TUR (My University, 2002)
[Abstract Not Available]
Türk veterinerlik ve hayvancilik dergisi: Editör'den mektup
Keywords: Animalia; editorial; veterinary medicine